Step-by-step explanation:
Subtract a from both sides
a-a+b-___=a-a
b-__=0
b=___
answer:b
Hope that helps :)
Answer:
Step-by-step explanation:
f * g = (x^2 + 3x - 4) (x+4)
open bracket
x((x^2 + 3x - 4) + 4 (x^2 + 3x - 4)
x³ +3x²-4x+x²+12x-16
x³+3x²+x²-4x+12x-16
x³+4x²+8x-16 (domain is all real numbers.
f/g = (x^2 + 3x - 4)/(x+4)
factorising (x^2 + 3x - 4)
x²+4x-x_4
x(x+4) -1 (x+4)
(x+4)(x-1)
f/g = (x^2 + 3x - 4)/(x+4) =(x+4)(x-1)/(x+4) = (x-1)
Before factorisation, this was a rational function so the domain is all real numbers excluding any value that would make the denominator equal zero.
Hence I got x - 1, and x cannot equal -4
So the domain is just all real numbers without -4
Answer:
:D
Step-by-step explanation:
Answer:
65%
Step-by-step explanation:
STEP ONE:
Find unit percent of 40. You should get 0.4.
STEP TWO:
Divide 26 by 0.4 and get 65.
So, the answer is 65%.